Estimating and Controlling the Renewable Microgrid States Using IoT Infrastructure. Issue 4 (8th October 2019) - Rana, Md Masud; Bo, Rui; Chen, Haotian
Abstract: This paper considers the optimal filter design issue for microgrid state estimation and stabilisation under packet loss conditions. The considered internet of things (IoT) technologies collect system state information from sensors and send control messages to actuators where they are connected over a lossy communication network. From signal processing point of view, this paper develops an optimal state estimation algorithm using the mean squared error principle. Then a feedback controller is designed under the condition of packet dropouts in the communication network. Finally, the convergence of the developed algorithm is numerically shown. The performance of the proposed schemes are demonstrated using the renewable microgrid.